The Role of Teacher Stimulus in Children's Language Development - Tatik Dwi Cahyani; Zulkarnaen Zulkarnaen (Universitas Muhammadiyah Ponorogo, 2023)
This research aimed to analyze the role of teacher stimulation in developing language skills in early childhood. The research method used descriptive qualitative methods. The data collection technique applied the survey method. The research respondents were 30 students of RPL PG PAUD (Early Childhood), Universitas Muhammadiyah Surakarta, in the Year of 2021. The results of this study indicated several things the teacher has implemented in stimulating the development of language skills in children by using all aspects of Yawkey stimulation. It includes developing language fluency at 80%, integrating language skills in everyday life reaching 80%, syntax development reaching 63.33%, development of vocabulary mastery being 73.33%, and the development of the ability to express oneself reaching 66.67%. Stimulation of developing language skills in early childhood carried out by teachers has been well implemented.